Factors to Motivational Affecting Influence of entrepreneurship Intention Among Undergraduate Students: A Case Study of Rajapruk University and Southeast Bangkok University - Vashararangsi, Panida (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2025)
This research article aims to: 1) Analyze the level of entrepreneurial motivation among undergraduate students at Rajapruk University and Southeast Bangkok University. 2) Compare intrinsic and extrinsic entrepreneurial motivations among these students. 3) Examine the influence of intrinsic motivational factors (push factors) and extrinsic motivational factors (pull factors) on the entrepreneurial intentions of undergraduate students. This is a survey-based research study. The sample consists of 312 undergraduate students from Rajapruk University and Southeast Bangkok University, selected through simple random sampling. The research instrument used was a questionnaire. The findings indicate that extrinsic motivation, specifically the perception of business opportunities, and intrinsic motivation, particularly necessity-driven factors, significantly influence entrepreneurial characteristics. The results reveal a combined variance explained by both types of motivational factors. Notably, extrinsic motivation related to identifying business opportunities positively influences entrepreneurial characteristics (β = 0.674, p < .01). In contrast, intrinsic motivation driven by necessity has a negative influence (β = -0.524, p < .01). Together, these factors explain 52.2% of the variance in entrepreneurial characteristics. The results highlight that fostering the ability to identify business opportunities is more critical than encouraging entrepreneurship driven by necessity. The research results show that the extrinsic motivation for doing business because of seeing opportunities and the intrinsic motivation for doing business because of necessity influence entrepreneurial characteristics. Both variables co-vary. Each aspect of the motivation factors consists of extrinsic motivation for doing business because of seeing opportunities, which has a statistically significant positive influence on entrepreneurial characteristics: (1) Extrinsic motivation for doing business because of seeing opportunities increases entrepreneurial characteristics, while intrinsic motivation for doing business because of necessity has a statistically significant negative influence on entrepreneurial characteristics. (2) Intrinsic motivation for doing business because of necessity increases entrepreneurial characteristics. (3) Extrinsic motivation for doing business because of seeing opportunities influences entrepreneurial characteristics. (4) Intrinsic motivation for doing business because of necessity which has an influence on the characteristics of being an entrepreneur. Therefore, it is accepted that motivation factors have an influence on being an entrepreneur of undergraduate students.